THE IMPORTANCE OF HEALTHCARE IN ENSURING ECONOMIC GROWTH IN AGRICULTURE - Ergashev Gayratjon Urolovich (Web of Journals Publishing, 2025)
Agriculture plays a crucial role in the economic development of many nations, especially in rural and developing regions. However, sustainable growth in this sector is highly dependent on the health and well-being of agricultural workers. This paper examines the interrelation between healthcare and economic growth in agriculture, emphasizing how improved health services, nutrition, and occupational safety can directly impact productivity, income generation, and long-term development.
Keywords: Resilience, healthcare, labor-intensive, exposure, chronic illnesses, backbone, sustainable, absenteeism.